Palladium nanoparticles on carbon nanotubes as catalysts of cross-coupling reactions - Cornelio, Benedetta; Rance, Graham A.; Laronze-Cochard, Marie; Fontana, Antonella; Sapi, Janos; Khlobystov, Andrei N. (Royal Society of Chemistry, 2013)
The macroscopic properties of composite nanotube-nanoparticle superstructures are determined by a complex interplay of structural parameters at the nanoscale. The catalytic performance of different carbon nanotube-palladium nanoparticle catalysts, where nanoparticles were formed either directly onto nanotubes or preformed prior to deposition on nanotubes using different types of surfactants, were tested 10 in cross-coupling reactions. The decoration of multi-walled carbon nanotubes with preformed thiolate-stabilised palladium nanoparticles yielded the optimum catalyst, exhibiting high activity and stability towards carbon-carbon bond formation and excellent recyclability, retaining high activity from cycle to cycle. The type of carbon nanotube support has pronounced effects on the density of deposited nanoparticles, with more polarisable MWNT able to uptake the highest number of nanoparticles per unit 15 surface area as compared to other carbon nanostructures (MWNT>DWNT>SWNT~GNF). Microscopic investigation of the nanoscale morphology found that nanoparticles increase in size during catalysis. The extent of growth is dependent on the type of nanocarbon support, with wider MWNT possessing lower curvature and thus retarding the growth and coalescence of nanoparticles to a greater extent than other carbon nanostructures (SWNT>>DWNT>MWNT~GNF). The type of halogen X in the C-X bond 20 activated by palladium appears to influence the evolution of nanoparticles during catalysis, with X=Br having the greatest effect as compared to X=Cl or I. Overall, preformed thiolate-stabilised palladium nanoparticles deposited on MWNT from solution was found to possess the most functional catalytic properties, with optimum activity, stability and recyclability in a range of cross-coupling reactions.